Validation of the Reveal® 3-D for Peanut Lateral Flow Test: AOAC Performance Tested MethodSM 111901. (23rd July 2020) - Le, Quynh-Nhi; Vance, Alexis; Bakir, Nawal; Almy, Dave; Slenk, Emily; Roman, Brooke; Klass, Nicole; Bastin, Benjamin; Donofrio, Robert
Abstract: Background: Reveal ® 3-D for Peanut is an immunochromatographic, lateral flow test for qualitative detection of peanut residue in food manufacturing and food preparation settings. The test can detect low ppm levels of peanut in clean-in-place (CIP) rinses and in swabs from environmental surfaces and can serve as a tool in managing allergen risk. Objective: The objective of the study was to validate the lateral flow method for detection of peanut in CIP rinses, specifically water, peroxyacetic acid/hydrogen peroxide, and quaternary ammonium compound rinses, and in swabs taken from stainless steel and plastic surfaces. Methods: CIP rinses spiked with low levels of peanut were tested, as were surfaces inoculated with peanut. Specificity and assay interference were assessed in testing of food commodities with and without added peanut. Assay robustness and test kit stability and consistency testing were also performed. Results: Results demonstrated that the lateral flow test can detect peanut in CIP rinses in the range of 2–4 ppm and in environmental surface swabs in the range of 3–4 µg/100 cm 2 . Results of specificity testing with 29 common food items showed lack of cross-reactivity, and potential assay interference only from walnut. Data from stability trials supports expiration dating for the kit of up to 23 months post-manufacture. Conclusions and Highlights: The lateral flow test is a sensitive, specific, and rapid method for detection of low levels of peanut residue in CIP rinses and environmental samples and can be an important component in a comprehensive allergen risk management program.